Efektivitas Game English Whisper dalam Meningkatkan Keterampilan Berbahasa Inggris pada Siswa SMP 19 Makassar - Dien Afni Ariyati; Rostina Rostina (Jurnal Pengabdian Masyarakat Nusantara, 2024)
This study aims to improve proficiency in four English language skills—reading, listening, writing, and speaking—by utilizing the English Whisper game method in English learning. It employs a descriptive qualitative approach, emphasizing observation and the evaluation of student performance throughout the learning process. Data were gathered through direct observation of students' ability to comprehend and communicate information using this game-based method. The research findings indicate that the English Whisper method is effective in improving students' abilities in all four English language skills. In the reading aspect, students demonstrated better comprehension and translation of given sentences. In listening, there was an improvement in understanding orally delivered messages. In writing, students were able to reproduce the sentences they heard more accurately. Meanwhile, in speaking, students became more confident in expressing sentences orally. Besides enhancing language skills, the English Whisper method also creates a more enjoyable, interactive learning environment and motivates students to participate actively in the learning process. Thus, this method can serve as an innovative and engaging learning alternative to improve English language proficiency in the classroom.